Understanding the Interplay Between Health Disparities and Epigenomics - Mancilla, Viviana J.; Peeri, Noah C.; Silzer, Talisa; Basha, Riyaz; Felini, Martha; Jones, Harlan P.; Phillips, Nicole; Tao, Meng-Hua; Thyagarajan, Srikantha; Vishwanatha, Jamboor K. (Frontiers in Genetics, 2020)
Social epigenomics has emerged as an integrative field of research focused on identification of socio-environmental factors, their influence on human biology through epigenomic modifications, and how they contribute to current health disparities. Several health disparities studies have been published using genetic-based approaches, however, increasing accessibility and affordability of molecular technologies has allowed for an in-depth investigation of the influence of external factors on epigenetic modifications (e.g. DNA methylation, micro-RNA expression). Currently, research is focused on epigenetic changes in response to environment, as well as targeted epigenetic therapies and environmental/social strategies for potentially minimizing certain health disparities. Here we will review recent findings in this field pertaining to conditions and diseases over lifespan encompassing prenatal to adult stages.